THE PRACTICE OF ENGLISH LANGUAGE TEACHING USING CAMBRIDGE PRIMARY CURRICULUM IN SDK KALAM KUDUS SURAKARTA - Pratiwi, Anisa Nur (Kajian Linguistik dan Sastra, 2018)
Considering the importance of English in today's rapid globalized world, the number of schools whose curriculum adhering to an international curriculum has increased in Indonesia. One of the international curricula is Cambridge Curriculum set in sequence from Cambridge Primary for primary schools to Cambridge ICGSE for high schools. As Cambridge Primary students are justified to speak naturally in English, this article described the practice of English teaching inside English as a Second Language (ESL) class for the 3rd grade in SDK Kalam Kudus, Surakarta. The main inquiry areas were teaching approaches, materials, activities and assessment. Actual data were collected through in-depth interviews, intensive classroom observations, and teaching learning document collection in the forms of learning objectives and students’ work. The findings revealed that teaching and learning approaches followed the principle of metacognition and active learning in which a student-centre classroom was emphasized, while the teacher was autonomous to design the teaching approach. Classroom activities referred to course book exercises as the main materials which were made up with a balance combination of receptive and productive skills. Interactions between teacher and students were positive. Students demonstrated eager learning and participation as well as high competitive atmosphere. Assessment was divided into formative assessment which was carried out every meeting by the teacher and summative assessment which was taken in the end of a learned chapter and school term.Key words: English language teaching, Cambridge Primary Curriculum, English for Primary School